Relationship Between Absorptive Capacity and Innovation Ambidexterity: Mediating Role of Entrepreneurial Orientation - HAMDI, Rahma (LPPM of NAROTAMA UNIVERSITY, 2024)
The literature in management sciences highlights the importance of entrepreneurial orientation as a lever to enhance productivity, competitiveness, and strengthen the position of companies. Globally, businesses are increasingly investing in developing their innovation capabilities to meet the demands of the digital economy and the